اصلاح العدالة العقابية في الجزائر - لعلالي سمية; جفافلية نرجس (My University, 2023)
Abstract : Due to the inability of custodial punishment, especially for a short period, to achieve its objectives, Algeria, like other countries, tended to shift from traditional punitive justice to alternative punitive justice, tending towards abandoning custodial punishment and replacing it with other alternatives. Therefore, the problematic of this study revolved around the adequacy of the alternative penalties adopted by the Algerian legislator in reform and rehabilitation and their effectiveness in combating the criminal phenomenon. The study concluded that despite the strenuous efforts made to achieve this, the approved alternatives remain insufficient due to the continuous increase in crime rates and recidivism. :الملخص نظرا لعجز العقوبة السالبة للحرية خاصة قصيرة المدة عن تحقيق أغراضها اتجهت الجزائر كغيرها من الدول إلى التحول من العدالة العقابية التقليدية إلى عدالة عقابية بديلة، تتجه نحو التخلي عن العقوبة السالبة للحرية واستبدالها ببدائل أخرى. لذلك تمحورت إشكالية هذه الدراسة حول مدى كفاية العقوبات البديلة التي اعتمدها المشرع الجزائري في الإصلاح والتأهيل ومدى فعاليتها في مكافحة الظاهرة الاجرامية. وقد خلصت الدراسة إلى أنه رغم الجهود الحثيثة المبذولة في سبيل تحقيق ذلك تبقى البدائل المعتمدة غير كافية نظرا للتزايد المستمر لمعدلات الجريمة والعود. Abstrait : En raison de l'incapacité de la peine privative de liberté, surtout pour une courte période, à atteindre ses objectifs, l'Algérie, comme d'autres pays, a eu tendance à passer de la justice punitive traditionnelle à la justice punitive alternative, tendant à abandonner la peine privative de liberté et à la remplacer par d'autres alternatives. Dès lors, la problématique de cette étude tournait autour de l'adéquation des peines alternatives adoptées par le législateur algérien en matière de réforme et de réhabilitation et de leur efficacité dans la lutte contre le phénomène criminel. L'étude a conclu que malgré les efforts acharnés déployés pour y parvenir, les alternatives approuvées restent insuffisantes en raison de l'augmentation continue des taux de criminalité et de récidive.